2022
DOI: 10.3389/fphar.2022.1103986
|View full text |Cite
|
Sign up to set email alerts
|

Cuproptosis-related lncRNA signatures predict prognosis and immune relevance of kidney renal papillary cell carcinoma

Abstract: Kidney renal papillary cell carcinoma (KIRP) has a high mortality rate and a poor prognosis. Cu concentrations differed significantly between renal cancer tissues and adjacent normal tissues. Cuproptosis is a newly identified cell death. Long non-coding RNAs (lncRNAs) play a crucial role in the progression of KIRP. In this study, we focused on constructing and validating cuproptosis-related lncRNA signatures to predict the prognosis of KIRP patients and their immune correlation. We created prognosis models usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…KIRP stands as the second most prevalent variant of renal cell carcinoma, making up around 15% of all such carcinomas(4-6). The prognosis of KIRP patients is highly variable, currently, there is no effective treatment for advanced-stage kidney renal papillary cell carcinoma (KIRP) (7)(8)(9)(10). So effective prognostic biomarkers are urgently needed for personalized treatment and follow-up strategies.…”
Section: Introductionmentioning
confidence: 99%
“…KIRP stands as the second most prevalent variant of renal cell carcinoma, making up around 15% of all such carcinomas(4-6). The prognosis of KIRP patients is highly variable, currently, there is no effective treatment for advanced-stage kidney renal papillary cell carcinoma (KIRP) (7)(8)(9)(10). So effective prognostic biomarkers are urgently needed for personalized treatment and follow-up strategies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a risk model constructed based on eight lncRNAs, including RNF139-AS1, LINC00996, NR2F2-AS1, AL590428.1, SEC24B-AS1, AC006566.1, UBE2Q1-AS1, and AL021978.1, could be used as an independent prognostic indicator for bladder urothelial carcinoma [ 27 ]. The same lncRNA profile associated with cuproptosis could be used to predict the prognosis and immune relevance of kidney renal papillary cell carcinoma, providing new potential therapeutic targets and prognostic markers for kidney renal papillary cell carcinoma patients [ 28 ]; however, the regulation mechanism of lncRNAs on cuproptosis-related genes in HCC is still unclear. Further analysis of cuprotosis-related lncRNAs can provide more diagnostic, prognostic, and therapeutic targets for patients with liver cancer; therefore, the identification of lncRNAs related to cuproptosis-related genes is of great significance for the clarification of underlying mechanisms of hepatocarcinogenesis and the investigation of new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, another study found that lncRNAs can be used as prognostic markers for tumors [19]. Recently, some studies found that lncRNAs were related to cuproptosis in many tumors, such as lung adenocarcinoma, hepatocellular carcinoma, osteosarcoma, kidney renal papillary cell carcinoma, and so on [20][21][22][23][24]. Therefore, it is necessary to develop prognostic biomarkers for early diagnosis and treatment by establishing lncRNA models in BLCA.…”
Section: Introductionmentioning
confidence: 99%